Histological structure of the double tooth pulp - M. Szczerba-Gwóźdź, Joanna; Sochaczewska-Dolecka, Agnieszka; Rahnama, Mansur; Jakiel, Joanna (Journal of Stomatology, 2017)
Introduction. Dental pulp is the remnants of the dental papilla. It fills the pulp chamber and is attached to periodontium through the apical foramen of a root. Double tooth is a disorder related to the increase in the size of a tooth. Aim of the study. To compare histological structure of the pulp of a lower third molar possessing the features of a double tooth with the histological structure of lower third molars with no dental caries. Material and methods. Histological examination of the pulp isolated from eleven lower third molars was performed. All teeth involved in the study were not carious and they were extracted in total. One tooth revealed the features of a geminated tooth. The remaining ten teeth displayed a typical anatomical structure. Having prepared the pulp isolated from the examined teeth, staining of the scraps with hematoxylin and eosin (H+E) was done allowing precise imaging of both cellular and tissue architectonics of the collected research material. Results. The analysed scraps revealed normal architectonics of dental pulp. In the peripheral part of the pulp oblong osteoblasts were identified. Cytoplasm of osteoblasts stained light pink and oval cell nuclei of odontoblasts stained basophilic. Poorly differentiated, acellular layer of the connective tissue forming cellfree zone of Weil was observed under the layer of odontoblasts. Conclusion. In the pulp of a double tooth a larger number of blood vessels was observed. The pulp of a double tooth revealed normal structure, with no inflammations. It is difficult to obtain the pulp